EVOLUTION OF SEX DETERMINATION SYSTEMS WITH HETEROGAMETIC MALES AND FEMALES IN SILENE. (2nd September 2013) - Slancarova, Veronika; Zdanska, Jana; Janousek, Bohuslav; Talianova, Martina; Zschach, Christian; Zluvova, Jitka; Siroky, Jiri; Kovacova, Viera; Blavet, Hana; Danihelka, Jiri; Oxelman, Bengt; Widmer, Alex; et al.
<x xml:space="preserve">Abstract</x> The plant genus Silene has become a model for evolutionary studies of sex chromosomes and sex‐determining mechanisms. A recent study performed in Silene colpophylla showed that dioecy and the sex chromosomes in this species evolved independently from those in Silene latifolia, the most widely studied dioecious Silene species. The results of this study show that the sex‐determining system in Silene otites, a species related to S. colpophylla, is based on female heterogamety, a sex determination system that is unique among the Silene species studied to date. Our phylogenetic data support the placing of S. otites and S. colpophylla in the subsection Otites and the analysis of ancestral states suggests that the most recent common ancestor of S. otites and S. colpophylla was most probably dioecious. These observations imply that a switch from XX/XY sex determination to a ZZ/ZW system (or vice versa) occurred in the subsection Otites. This is the first report of two different types of heterogamety within one plant genus of this mostly nondioecious plant family.